Global Ocean dimethylsulfide photolysis rates quantified with a spectrally and vertically resolved model - Galí, Martí (2023)
Dimethylsulfide (DMS) is a gas produced by marine microbes that, once emitted to the atmosphere, affects the formation of atmospheric particles (aerosols) and clouds, and hence climate. Several processes can remove DMS from the upper ocean layer, therefore controlling DMS emissions. One such process that has not been accurately quantified hitherto is the oxidation of DMS by chemical reactions driven mostly by UV radiation. Using a model that combines satellite observations and in situ data, here we show that DMS photolysis varies across regions and seasons; and quantify global photochemical DMS removal from the surface ocean at around 20 million tons of sulfur per year, 30% less than DMS emission to the atmosphere. Our best estimates are not compatible with estimates from simplified equations for DMS photolysis that are currently used in the numerical models that inform climate projections, stressing the need to improve those models.